The Balkans between the EU and NATO: Focusing on the Former Yugoslavia - Mamoru Sadakata (Romanian Journal of European Affairs)
The fragmentation of Yugoslavia has wrought extensive political and social changes in the Balkans and Europe more generally. After the collapse of communism and the breakup of Yugoslavia, many Balkan countries have transformed their political system and have begun to forge new foreign and security policy. Some of them have already joined the EU and NATO, and some are about to access these organizations. But the Western Balkan states seem to be farther in the future. In regard to the former Yugoslavia, the United States, European states and international organizations, such as the EU, NATO and UN, have attempted to engage and manage this breakup on an individual and collective basis. They have greatly influenced the process of the post-conflict nation building of this region. From this viewpoint, the paper discusses the political and social transformation of the Balkans after the breakup of the Yugoslav conflict, and the role of the EU and NATO in the process of the democratization and nation building in the former Yugoslavia. Moreover, attention is paid to the features of the involvement of the EU and NATO in the former Yugoslav conflict. In the process of Yugoslav fragmentation one can see the ‘Eastern Question’ revisited and the ‘Powder keg of Europe’ once again rising to its brim.